Experimental investigation on ignition, combustion and micro-explosion of RP-3, biodiesel and ethanol blended droplets. (September 2020) - Meng, Kesheng; Bao, Lin; Shi, Yubao; Han, Kai; Lin, Qizhao; Wang, Chengjun
Highlights: ·The ejection and micro-explosion accelerate the droplet combustion. ·The BD60R10E30 droplet is most prone to micro-explosion. ·The micro-explosion intensity of BD60E40 and BD60R10E30 droplets are compared. Abstract: Based on an infusion set, measuring cylinder and different types of micro needles, a method for measuring the volume of micro-droplet was established. The same volume of aviation fuel (RP-3), biodiesel and ethanol mixed droplets were sent to a heatable experimental device to study the combustion characteristics. Through a movable slide rail with adjustable speed, the mixed droplets suspended on the high-temperature resistant wire were transported to a distance of about 2 mm from the preheating plug for heating. The ingle-lens-reflex (SLR) camera and a high-speed camera were used to capture the ignition characteristics and instantaneous combustion characteristics of mixed droplets during heating, respectively. The burning mixed droplets video captured by the SLR camera was processed into color pictures by Adobe Premiere Pro CC software. Through the processing and analysis of these images, the ignition, combustion and micro-explosion characteristics of mixed droplets during combustion were studied. The equation for calculating the micro-explosion intensity was established, the micro-explosion intensity of binary mixed droplets and ternary mixed droplets was calculated and analyzed.